Improvement of peanut milk - Enciso, Joan Aura L. (1977)
The study was conducted to improve the acceptability of peanut milk. The effects of the peeling method, addition of vanillin, and the addition of stabilizers on peanut milk quality were determined. For the first phase, two batches of peanut milk were prepared; one from lye peeled nuts, the other from roast peeled peanuts. For each batch, milk samples with 0, 0.3, and 0.5% vanillin were prepared and subjected to sensory evaluation. Based on sensory evaluation and protein determination results, the best sample is the unflavored milk from roast peeled peanuts. Unflavored milk from roast peeled peanuts was prepared for the second phase of the study. To determine the effect of stabilizers, a third of the milk was incorporated with 0.2% sodium carboxymethylcellulose (CMC), and another third with 0.2% carrageenan. These were compared with the last third of the milk which was left without a stabilizer. Based on sensory evaluation results, protein dispersibility and on the appearance of the milk, the best sample is the one with added CMC as stabilizer.
Thesis (B.S.)--University of the Philippines, Quezon City.
Keywords: Peanut milk; Peanut products